Baby - MacLachlan, Patricia (New York : Bantam Doubleday Dell Books for Young Readers, 1993)
Taking care of a baby left with them at the end of the tourist season helps a family come to terms with the death of their own infant son.
"A Yearling book."
Wilson's Children
School Library Journal
Publisher's Weekly
5.4
5-8
Keywords: Babies -- Fiction; Grief -- Fiction; Islands -- Fiction; Infants -- Fiction; Grief -- Fiction; Islands -- Fiction